The effectiveness of community mediating role at rural level disputes: a study of addalaichenai mediation board coastal area in ampara district in sri lanka - Jabbar, M.A.; Manivasagar, A.V. (University of Jaffna, 2012)
The disputes are unavoidable in human life and it is considered to produce destructive consequences. Hence, there are number of mechanisms used to settle the rural level disputes. Among those mechanisms the community mediation is to be a successful tool for dispute management among rural level disputing parties. The community mediation is a process of devolving the judicial power from the state to the people for meaningful response to the rural level disputes. In this context, the study attempts to analysis the practices of the Addalaichenai Mediation Board and to identify the challenges which are blocking the smooth functioning of community mediation board in Addalaichenai. Further, the study attempts to evaluate the effectiveness of the community mediatory role of Addalaichenai Mediation Board. This study is based on interpretative method owing to their practical merits with using quantitative and qualitative survey. Above stated objectives have been achieved by studying both primary and secondary data. The study reveals that the community mediation has been considered as a successful mechanism for dispute management at rural level. This system has been adopted to settle and manage the rural level disputes in Addalaichenai. However, the effectiveness of community mediatory role at this area has been questioned due to number of problems.
Keywords: Community mediation; Dispute settlement and management; Mediation Board